Equivalencia de los niveles séricos de hierro tras la ingesta de extracto de bazo de bos taurus l. y tabletas de sulfato ferroso genérico - Guerra Ñique, Diana Paola (2009)
Were compared iron serum levels originating from extrac spleen of Bos Taurus L. and generic ferrous sulphate tablets, using Iron-Ferrozine of BioSystems's method. The study was realized in 16 apparently healthy volunteers, they in the first period a ferrous sulphate tablet was administered for oral route, and in the second period they consumed 300g of extrac spleen of Bos Taurus L. with 250 ml of water, the determinations being realized to the 0,5 hours, 1 hour, 4 hours, 6 hours and 8 hours in both periods respectively previous taking of a basal sample. The concentrations average obtained for the extrac spleen of Bos Taurus L. were: 0,5 hours (360,635 ug/dl), 1 hour (673,13 ug/dl), 2 hours (810,08 ug/dl), 4 hours (415,415 ug/dl), 6 hours (181,977 ug/dl) and 8 hours (73,24 ug/dl);and for ferrous sulphate tablets were: 30 min (27,75 ug/dl), 1 hour (83,22 ug/dl), 2 hours (128,65 ug/dl), 4 hours (301,12 ug/dl), 6 hours (438,23 ug/dl) and 8 hours (266.59 ug/dl). Of thr obtained results there concludes that the ingestion of extrac spleen of Bos Taurus L. had a fast absorption and a high iron serum levels, in comparison with the generic ferrous sulphate tablets